Controls and provisions of electronic financial papers (a comparative jurisprudential study) - Alshaikhi, Mohammed Khalil Mohammed (Journal of Islamic Sciences, 2024)
The importance of the study is that the process of dealing in electronic securities is one of the main pillars in the contemporary financial markets. Therefore, this study sheds light on something very important and enlightens the way for researchers and science students to delve into similar topics, as it is considered one of the most attractive transactions that attract dealers in financial markets.The study aimed to clarify the legal ruling on dealing with electronic securities, and to clarify what is meant by electronic securities, and to indicate the positive and negative effects of electronic securities, and to clarify the basic features of this topic. What are the conditions for dealing in electronic securities? What is the jurisprudential conditioning for dealing with electronic securities?To achieve these research goals, the researcher relied on several approaches as follows: the inductive approach, the analytical approach, and the comparative approach.The study reached a set of results; Perhaps the most important of them are the following:The inadmissibility of dealing with usurious interests, by paying or receiving any fees for swap deals, and the inadmissibility of trading in prohibited shares that are with companies that deal with usurious interests or manufacturing forbidden things.The research also recommended several proposals; The most important of them:Dealing with such issues by studying, by conducting scientific research in universities or by holding various competitions that urge the study of these contemporary jurisprudential aspects, in addition to holding conferences and seminars that show the ruling on contemporary financial transactions.
Keywords: electronic securities; financial markets; Contemporary jurisprudence; Islamic economy